Co-Desistance From Crime: Engaging the Pro-Social Dimensions of Co-Offending - Halsey, Mark (The British journal of criminology, 2023)
Drawing on primary data from a unique crime prevention initiative in Australia, this article examines how a small group of co-offenders harnessed the pro-social dimensions of their offending to co-desist from crime. We focus particularly on the evolving nature of group dynamics and the roles played by policing (including non-policing), innovative ‘24/7’ casework, and the provision of a culturally safe divergent setting in the emergence of co-desistance scenarios. We show how initial apprehensions around co-offenders associating in the community were unfounded and in fact proved key to the success of such an approach. Building on the supported desistance literature, the article positions co-desistance as a related but distinct concept worthy of further study in its own right.